Bioactive Polyphenols from Pomegranate Juice Reduce 5-Fluorouracil-Induced Intestinal Mucositis in Intestinal Epithelial Cells - Giacomo Pepe; Shara Francesca Rapa; Emanuela Salviati; Alessia Bertamino; Giulia Auriemma; Stella Cascioferro; Giuseppina Autore; Andrea Quaroni; Pietro Campiglia; Stefania Marzocco (Antioxidants, 2020)
Intestinal epithelial cells (IECs) play a pivotal role in maintaining intestinal homeostasis. Different noxious agents, among them also anticancer therapies, can impair intestinal epithelial integrity triggering inflammation and oxidative stress. A frequent complication of chemotherapy is gastrointestinal mucositis, strongly influencing the effectiveness of therapy, increasing healthcare costs, and impairing patients’ quality of life. Different strategies are used to treat gastrointestinal mucositis, including products from natural sources. Our study focused on the effect of pomegranate (Punica granatum L.) juice extract on IEC-6 cells, both during inflammatory conditions and following treatment with 5-fluorouracil (5-FU). The polyphenolic profile of pomegranate juice was characterized in detail by Online Comprehensive two dimensional Liquid Chromatography-Mass Spectrometry. The evaluation of pomegranate juice extract in IEC-6 indicates a significant inhibition in proinflammatory factors, such as cytokines release, cyclooxygenase-2 and inducible nitric oxide synthase expression, and nitrotyrosine formation. Pomegranate also inhibited oxidative stress and adhesion protein expression. In 5-FU-treated IEC-6, pomegranate also inhibited both inflammatory and oxidative stress parameters and apoptosis. It promoted wound repair and tight junction expression. These results suggest a potential use of pomegranate as an adjuvant in the treatment of intestinal inflammatory and oxidative stress states, which also occur during chemotherapy-induced mucositis.